Introduction to University Calculus for “Bunkei’’ Students in Waseda - Takuya Sobukawa; Satoru Takagi; Hiroaki Uesu (Высшее образование в России, 2019)
In these days, mathematics is one of the most important tools for any person. However, in Japan, many students hate and avoid mathematics in their high school age. In Waseda University, one of the biggest and oldest private universities in Japan, special curriculum is constructed for such “Bunkei’’ students who major in social or human science.